(3JYdjb TQM GdCUhd GdNeSIs - (3bhGe GdOjf eG fcOjf CMeO Hf GdMSjf Hf CHi gGTe GdeYQha HJTOjhs; (3YHO GdLHGQ Hf CMeO GdgePGfj GdGSJQGHGOj,J (B415 (3g` s ((3eMeO Hf YHO Gddg Hf eMeO Hf EHQGgje Hf eMeO s)
(3ChdgG (B:s
(3HOC bGVi GdbVGg YHO GdLHGQ ai GdTQM HSDGd GdCUhd GdNeSI Ef SCd SGFd abGd (B: (3eG Chd eG ChLH Gddg JYGdi Ydjc , abd GdfXQ s
(3BNQgG (B:s
(3hjchf GdeQGO Hg Cf Sgd Gddg di Pdc hdWa di ajg agPg LedI eG jLH Cf jMUd ai gPG GdHGH hEPG bO CJjfG Ydi Pdc haQZfG efg aEfG fbWY YfOg GdcdGe hfNJe Hg GdcJGH s
(3cJHJ GdYfhGfGJ HGdMeQIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds